Biomass and Industrial Wastes as Resource Materials for Aerogel Preparation: Opportunities, Challenges, and Research Directions - Asim N.; Badiei M.; Alghoul M.A.; Mohammad M.; Fudholi A.; Akhtaruzzaman M.; Amin N.; Sopian K. (American Chemical Society, 2023)
Biomass; Industrial research; Industrial wastes; Alternative materials; Commercial applications; Economic development; Preparation method; Recycling wastes; Research challenges; Resource materials; Sustainable resources; Aerogels